BEST PRACTICES IN BUSINESS MANAGEMENT - Paidi W.S; Akhmad Hairul Umam (Journal of Management and Leadership, 2022)
Running the trading or business in general is aimed at gaining the long-term profit. However, the trading made merely to earn profit without taking into account the service as well as the consumers’ satisfaction will not be sustainable. The objective of this research is to socialize the business in the manner applied by the Prophet Rasulullah Shollallahu’alaihi Wassalam. The research method is analytic descriptive. Data or information obtained is sourced from the books, journals and various sources relevant to this journal topic. In running the business, Rasulullah always upholds the honesty, ethic, has never reduced the scale and size, free of riba (usury), does not practice the monopoly, is consistent in maintaining the mandate, is tolerant and pays the wages of his assistants before their sweats are dry as well as pays attention to the customers’ satisfaction. The smart Rasulullah SAW in running the business always focuses on the market shares he masters in. He is able to penetrate the new market, and very superior in conquering the hearts of the customers who will buy and use the goods he traded.